2017
DOI: 10.1007/s10461-017-1811-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of and Adherence to an Antiretroviral-Based Vaginal Microbicide among Pregnant Women in the United States

Abstract: The MTN-008 trial was the first multi-dose study conducted to evaluate the safety of a microbicide gel (2:1 randomized to tenofovir 1% or hydroxycellulose (HEC) placebo gel) during pregnancy. The study aim was to evaluate safety, tolerability and pharmacokinetics of the study products. Procedures included daily gel administration, with Day 0 and Day 6 in clinic, and Days 1–5 at home. Because pregnancy may pose unique challenges to consistent gel use and acceptability, evaluation of adherence and acceptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In previous studies assessing acceptability of potential intravaginal methods for HIV prevention, including diaphragms, gels, and rings, women's opinions have generally been very positive, particularly when measured quantitatively [8,[19][20][21][22]. Here, we found that women reported liking all the products, with the film more highly rated in Zimbabwe.…”
Section: Discussionmentioning
confidence: 48%
“…In previous studies assessing acceptability of potential intravaginal methods for HIV prevention, including diaphragms, gels, and rings, women's opinions have generally been very positive, particularly when measured quantitatively [8,[19][20][21][22]. Here, we found that women reported liking all the products, with the film more highly rated in Zimbabwe.…”
Section: Discussionmentioning
confidence: 48%
“…[49][50][51][52] Despite mixed efficacy findings for products such as tenofovir gel 53,54 and the Phase III randomized placebocontrolled FEM-PrEP clinical trial of a daily oral dose of tenofovir disoproxil fumarate and emtricitabine, 55 microbicides may offer additional HIV prevention options for women with strong acceptability. [56][57][58] Yet, there remains a challenge to educate and offer PrEP to women experiencing violence.…”
Section: Discussionmentioning
confidence: 99%
“…Other work suggests product features may also affect adherence. For gels, excessive leakage was a frequent complaint, leading women to not insert the full recommended dosage [ 14 ]. Some women questioned whether this leakage would reduce efficacy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%